Dual-channel gas moisture analyzer and the study of its static metrological characteristics - Bilynskyi, Y. Y.; Horodetska, O. S.; Onushko, V. V.; Knysh, B. P. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Dual-channel infrared gas moisture analyzer with the feedback is suggested in the paper, the transformation function, and static metrological characteristics are obtained, namely: the nominal conversion function, absolute and relative error of nonlinearity, absolute multiplicative and additive errors.